A Framework for Asynchronous Collaboration Around Multimedia and its Application to On-Demand Training - Bargeron, David M.; Grudin, Jonathan; Gupta, Anoop; Li, Francis; Sanocki, Elizabeth (1999)
Delivering educational content on-demand is increasingly important for universities and corporations, and support for asynchronous collaboration is a key requirement. A multimedia annotation system tightly integrated with email provides a powerful platform to build such functionality. Building on top of our early work on multimedia annotations [2], we present new user-interface and system extensions to support asynchronous collaboration for on-demand training. We report results from a real-world case study on the effectiveness of our system, including student experience, instructor experience, and appropriateness of user interface. Overall, the student experience was very positive: students were delighted to have the flexibility of on-demand delivery, while at the same time they benefited from the collaborative features provided by our interface.